2021
DOI: 10.3389/fmolb.2021.662792
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Systemic and Local Inflammation Induced by Nasal Polyposis: Role of the Allergic Phenotype

Abstract: Chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by persistent symptoms associated to the development of nasal polyps. To this day, the molecular mechanisms involved are still not well defined. However, it has been suggested that a sustained inflammation as allergy is involved in its onset. In this exploratory study, the aim was to investigate the effect of the allergic status in the development of CRSwNP. To achieve this, we recruited 22 patients with CRSwNP and classified them in non-allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…From a practical point of view, it uses very sensitive and specific techniques, such as LC-MS, which allows the simultaneous detection of a great variety of metabolites in each biological sample. 23,24 In this study, we performed an untargeted metabolomic analysis in all samples from each experimental group, what results, after a complex and laborious statistical analysis, into the identification of several significant signals that conform the metabolomic signature of UC group. Therefore, this study should be understood as exploratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a practical point of view, it uses very sensitive and specific techniques, such as LC-MS, which allows the simultaneous detection of a great variety of metabolites in each biological sample. 23,24 In this study, we performed an untargeted metabolomic analysis in all samples from each experimental group, what results, after a complex and laborious statistical analysis, into the identification of several significant signals that conform the metabolomic signature of UC group. Therefore, this study should be understood as exploratory.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the metabolome has been described to be closely linked to the phenotype of a disease and can be an extremely useful tool when evaluating the effect of treatments. From a practical point of view, it uses very sensitive and specific techniques, such as LC‐MS, which allows the simultaneous detection of a great variety of metabolites in each biological sample 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences in comparing eosinophilic granulocyte counts in the polyp tissue between the SIgE‐positive and the SIgE‐negative groups, which suggested that the eosinophilic granulocytes might not increase when CRS w NP patients have allergic reactions. It suggests that the relationship between the general allergic reaction status and the degree of infiltration and activation of eosinophilic granulocyte in local tissues is uncertain 7,8 . It shows that the stimulation of sensitinogen to SIgE‐positive CRS w NP patients does not induce an inflammatory response of eosinophilic granulocyte in the nasal polyps, but there is an independent pathophysiological mechanism of inflammation maintenance 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of allergic reactions on the occurrence and development of CRS w NP is still inconclusive 7,8 . Still, available data support that serum IgE is associated with CRS w NP 9–11 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, by using non-targeted metabolomics in combination with transcriptomics and proteomics in different allergic disease severity models, we have identified new biological systems and associated promising potential biomarker candidates [ 16 , 17 , 18 , 19 , 20 ]. Furthermore, the combined analysis of these studies has allowed us to identify metabolites potentially related to energy metabolism, sphingolipid, phospholipid pathways, and platelet function associated with the severe phenotype [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%